Comparative evaluation of bioavailability of Botulinum toxin A complexed with Tizol (titanium glycerosolvate aquacomplex) versus pure Botulinum toxin A solution for bladder mucosa: an experimental study - S. V. Poroyskiy; D. V. Perlin; O. G. Srussovskaya; N. A. Goncharov; A. A. Kuznetsov; E. A. Morozov (Вестник урологии, 2024)
Introduction. For the treatment of overactive bladder syndrome (OAB), injection of botulinum toxin A (BoNT-A) has been shown to be effective. However, there is a need for a less invasive method for administering BoNT-A, which could significantly expand the treatment options for OAB.Objective. To assess the impact of tizol on the absorption of BoNT-A by the bladder mucosa and compare it to the individual absorption of BoNT-A.Materials & Methods. Dialysis through the mucous membrane of the сalf bladder was used as an experimental model to study changes in bioavailability of BoNT-A complexed with tisol (BoNT-A + T) and pure BoNT-A solution during in vitro experiment. After dialysis, the BoNT-A concentration in both samples was determined using a spectrophotometer. Dialysis curves were plotted according to the data obtained. Kruvchinsky equilibrium dialysis method was used to determine botulinum toxin A bioavailability. The UV spectrophotometry method was used to determine the concentration of BoNT-A in the acceptor medium by reaction of BoNT-A with Benedict's reagent.Results. It was established that the maximum concentration of BoNT-A diffused into the acceptor medium from the blend of the test substance with tizol after nine hours. The area under the curve for dialysis of BoNT-A + T exceeds the area under the curve of pure BoNT-A by almost 20%, suggesting an improvement in the drug's bioavailability when blended with tizol.Conclusion. Based on our experiment, it was found out that the BoNT-A + T has greater bioavailability than a solution of pure BoNT-A. However, the diffusion rate of the component mixture is sufficiently low.